The Influence of The Project-Based Learning Model on the Poetry Writing Skills of Class V Students of Pineleng State Elementary School - Monigir, Norma (International Journal of Information Technology and Education, 2023)
This research aims to improve poetry writing skills using the Project-based Learning Model for Class V Students of Pineleng State Elementary School. This research method uses quantitative research with the type of research being experimental research. This research was carried out to improve poetry writing skills using the Project Based Learning Model. The results of this research show that there is an influence of the use of project-based learning on learning outcomes for poetry writing skills, in line with the results of observations made. Based on the results of observations, there were changes in students where at the beginning of learning activities there were several students who were doing other activities or acting indifferent during the learning process. Observation results show that there are a large number of students who answer when asked questions and students who volunteer to work on questions on the blackboard. Students also begin to be active and confident in responding to answers from other students so that other students are also motivated to follow the lesson.